Nucleolin mediated pro‐angiogenic role of Hydroxysafflor Yellow A in ischaemic cardiac dysfunction: Post‐transcriptional regulation of VEGF‐A and MMP‐9. Issue 5 (7th March 2018) - Zou, Jiang; Wang, Nian; Liu, Manting; Bai, Yongping; Wang, Hao; Liu, Ke; Zhang, Huali; Xiao, Xianzhong; Wang, Kangkai
Abstract: Hydroxysafflor Yellow A (HSYA), a most representative ingredient of Carthamus tinctorius L., had long been used in treating ischaemic cardiovascular diseases in China and exhibited prominently anticoagulant and pro‐angiogenic activities, but the underlying mechanisms remained largely unknown. This study aimed to further elucidate the pro‐angiogenic effect and mechanism of HSYA on ischaemic cardiac dysfunction. A C57 mouse model of acute myocardial infarction (AMI) was firstly established, and 25 mg/kg HSYA was intraperitoneally injected immediately after operation and given once, respectively, each morning and evening for 2 weeks. It was found that HSYA significantly improved ischaemia‐induced cardiac haemodynamics, enhanced the survival rate, alleviated the myocardial injury and increased the expressions of CD31, vascular endothelial growth factor‐A (VEGF‐A) and nucleolin in the ischaemic myocardium. In addition, HSYA promoted the migration and tube formation of human umbilical vein endothelial cells (HUVECs), enhanced the expressions of nucleolin, VEGF‐A and matrix metalloproteinase‐9 (MMP‐9) in a dose‐ and time‐dependent manner. However, down‐regulation of nucleolin expression sharply abrogated the effect mentioned above of HSYA. Further protein‐RNA coimmunoprecipitation and immunoprecipitation‐RT‐PCR assay showed that nucleolin binded to VEGF‐A and MMP‐9 mRNA and overexpression of nucleolin up‐regulated the mRNA expressions of VEGF‐A and MMP‐9 in the HUVECs through enhancing the stability of VEGF‐A and MMP‐9 mRNA. Furthermore, HSYA increased the mRNA expressions of VEGF‐A and MMP‐9 in the extract of antinucleolin antibody‐precipitated protein from the heart of AMI mice. Our data revealed that nucleolin mediated the pro‐angiogenic effect of HSYA through post‐transcriptional regulation of VEGF‐A and MMP‐9 expression, which contributed to the protective effect of HSYA on ischaemic cardiac dysfunction.